2019
DOI: 10.1186/s12986-019-0350-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of nuts and unhealthy snacks with subclinical atherosclerosis among children and adolescents with overweight and obesity

Abstract: Background The process of atherosclerosis begins early in childhood and usually remains asymptomatic until later in life. Carotid intima-media thickness (cIMT) as a marker of subclinical atherosclerosis could identify early vascular alterations. Unhealthy snacks consumption is associated with obesity and other CVD risk factors in children and adolescents. The aim of this study is to investigate the association of different snack substitution and cIMT among overweight and obesity children and adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…In overweight and obese children 6 to 13 years of age, greater nut consumption was independently associated with lower carotid IMT (β=0.135 mm; P =0.009). 61…”
Section: Subclinical Atherosclerosismentioning
confidence: 99%
“…In overweight and obese children 6 to 13 years of age, greater nut consumption was independently associated with lower carotid IMT (β=0.135 mm; P =0.009). 61…”
Section: Subclinical Atherosclerosismentioning
confidence: 99%
“…Thus, we were able only to show a significant difference between children with T1DM and healthy controls, but the prognostic value of the obtained results remain unknown. This should be addressed in future studies, and it is especially important to assess whether subclinical atherosclerosis is a significant risk factor for development of cardiovascular diseases [20].…”
Section: Discussionmentioning
confidence: 99%
“…DF intake has a beneficial role on prevention of atherosclerosis and CHD, since it decreases TC and inflammation, two important factors that modify the development and progression of the disease (29,44). Recently, it was shown that in children and adolescents, the risk of increased carotid IMT was decreased by 59% by the intake of nuts (45).…”
Section: Dietary Fiber and Atherosclerosismentioning
confidence: 99%
“…Polyphenols also display antioxidant, anti-inflammatory and anti-apoptotic activities which can rescue cell life, decreasing cell degeneration and death. Their ingestion displays positive impacts on reduction of both morbidity and mortality as well as improvement on life span (30,45). Polyphenols can scavenge free radicals and reactive oxygen and nitrogen species, as well as they can reduce platelet activity, decreasing the risk of thrombosis.…”
Section: Polyphenolsmentioning
confidence: 99%